(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
Objective: This study aims to develop and validate a simple, cost-effective, and rapid UV-spectrophotometric method for the quantitative determination of Metronidazole in both its pure form and pharmaceutical tablet formulations. Methods: The analysis was conducted using 0.1 N NaOH as a solvent. Spectral measurements were performed at a maximum wavelength (λmax) of 320 nm using a Shimadzu UV-1800 spectrophotometer with 1 cm quartz cells. The method was strictly validated according to ICH guidelines. High-purity Metronidazole (>99%, Sigma-Aldrich) served as the standard, while commercial tablets (Cipla) were used for the formulation assay to evaluate the method’s practical applicability. Results: The method exhibited excellent linearity over the tested concentration range, with a regression equation of Y=0.0215x+0.0743 and a correlation coefficient (R2) of 0.9935. The percentage recovery ranged from 99.33% to 99.88%, demonstrating high accuracy and no significant interference from common excipients. Precision was confirmed by low relative error values (0.1129% to 1.1226%) for concentrations of 10–25 mg/mL. Both intra-day and inter-day precision remained within acceptable limits (Relative Error < 2%). The Limit of Detection (LOD) and Limit of Quantitation (LOQ) were determined to be 0.3069 μg/mL and 0.6302 μg/mL, respectively, indicating high sensitivity. Conclusion: The developed UV-spectrophotometric technique is accurate, precise, and robust. Its simplicity and reliability make it highly suitable for routine quality control and standard assays of Metronidazole in bulk and pharmaceutical dosage forms.